Scanning electron microscopy evaluation of the effect of etching agents on human enamel surface - Zanet, Caio G.; Arana-Chavez, Victor E.; Fava, Marcelo [UNESP] (My University, 2006)
Acid etching promotes microporosities on enamel surface, which provide a better bonding surface to adhesive materials. The purpose of this study was to comparatively analyze the microstructure of enamel surface after etching with 37% phosphoric acid or with two self-etching primers, Non-rinse conditioner (NRC) and Clearfil SE Bond (CSEB) using scanning electron microscopy. Thirty sound premolars were divided into 3 groups with ten teeth each: Group 1: the buccal surface was etched with 37% phosphoric acid for 15 seconds; Group 2: the buccal surface was etched with NRC for 20 seconds; Group 3: the buccal surface was etched with CSEB for 20 seconds. Teeth from Group 1 were rinsed with water; teeth from all groups were air-dried for 15 seconds. After that, all specimens were processed for scanning electron microscopy and analyzed in a Jeol 6100 SEM. The results showed deeper etching when the enamel surface was etched with 37% phosphoric acid, followed by NRC and CSEB. It is concluded that 37% phosphoric acid is still the best agent for a most effective enamel etching.
Keywords: Clearfil SE Bond; maleic acid derivative; non rinse conditioner; non-rinse conditioner; phosphoric acid; resin cement; water; adolescent; air; clinical trial; comparative study; controlled clinical trial; controlled study; dental acid etching; drug effect; enamel; female; human; male; methodology; porosity; randomized controlled trial; scanning electron microscopy; time; ultrastructure; Acid Etching, Dental; Adolescent; Air; Dental Enamel; Female; Humans; Male; Maleates; Microscopy, Electron, Scanning; Phosphoric Acids; Porosity; Resin Cements; Time Factors; Water